Variation in chronotype is associated with migratory timing in a songbird - Rittenhouse, Jeffrey L. (Biol Lett, 2019)
Like many organisms, birds exhibit daily (circadian) and seasonal biological rhythms, and within populations both daily and seasonal timing often vary among individuals. Because photoperiod interacts with the circadian rhythms of many organisms to induce seasonal changes in behaviour and physiology, it is hypothesized that differences in daily timing, called chronotypes, underpin differences among individuals in the timing of seasonal events. For seasonal events stimulated by increasing daylength, this hypothesis predicts a positive relationship between the timing of daily and seasonal activities of individuals, with advanced chronotypes expressing events earlier in the year. The few previous tests of this hypothesis have focused on seasonal reproductive timing in birds. However, the hypothesis predicts that this relationship should extend to other photoinduced seasonal events. Therefore, we tested whether variation in chronotype was associated with variation in spring migratory timing in a captive songbird model, the pine siskin (Spinus pinus). We found that pine siskins expressing migratory restlessness exhibited repeatable chronotypes in their timing of nocturnal activity. Further, chronotype was significantly associated with the onset date of migratory behaviour, consistent with the hypothesized relationship between chronotype and seasonal timing.